DE VELADO A (RE)VELADO: O PRECONCEITO CONTRA O ÍNDIO - Nascimento, Leandro José do (WEB REVISTA SOCIODIALETO, 2018)
O presente artigo discute o preconceito contra o indígena investigando como sua ocorrência configurou-se de maneiras distintas a partir das transformações pelas quais a sociedade passou. Com pressupostos teóricos de Gordon Alport (1897-1967)de José Léon Crochík (1996) e apoio metodológico de entrevistas semiestruturadas, o artigo tem por objetivo analisar a percepção e entendimento dos indígenas em relação ao preconceito e estereótipos, de modo a observar que figurações são construídas assim como qual a percepção do indígena sobre o tema. ABSTRACT: This article discusses the prejudice against the indigenous people considering an investigation to discover how their occurrence had innumerous and different configurations in according to the transformations through which society has passed. Based on the theoretical assumptions of Gordon Alport (1897-1967) and José Léon Crochík (1996) and including the methodological support of semi-structured interviews, the article aims to analyze the perception and understanding that indigenous people have about prejudice and stereotypes, in order to observe which figurations are constructed as well as what are their perceptions about the theme. KEYWORDS: Prejudice, Stereotypes, Indigenous People, Interview.